2007
DOI: 10.1121/1.2395915
|View full text |Cite
|
Sign up to set email alerts
|

Distortion product otoacoustic emission of symphony orchestra musicians before and after rehearsal

Abstract: The 2f1-f2 distortion product otoacoustic emission (DPOAE) and hearing levels are obtained for 12 normal-hearing symphony orchestra musicians both before and after their rehearsal. The DPOAE fine structures are determined and analyzed according to the character and prevalence of ripples. Hearing levels, DPOAE levels, and DPOAE fine structures before and after rehearsal are similar, indicating that no or marginal temporary change of the state of hearing were caused by the exposure. The data were further compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
(17 reference statements)
0
4
1
1
Order By: Relevance
“…This discrepancy might be explained by the fact that in their studies PTS was considered whereas in our study presumably TTS occurred and the underlying mechanisms for PTS and TTS are supposed to be different (Saunders et al, 1985;Nordmann et al, 2000). Reuter and Hammershøi (2007) reported that for symphony orchestra musicians, no significant shift occurred either in puretone thresholds or in DPOAE levels after 4 h of rehearsal (ca. 80 dB(A)).…”
Section: Factory Workers Exhibited Small Changes In Pure-tone Threshocontrasting
confidence: 64%
“…This discrepancy might be explained by the fact that in their studies PTS was considered whereas in our study presumably TTS occurred and the underlying mechanisms for PTS and TTS are supposed to be different (Saunders et al, 1985;Nordmann et al, 2000). Reuter and Hammershøi (2007) reported that for symphony orchestra musicians, no significant shift occurred either in puretone thresholds or in DPOAE levels after 4 h of rehearsal (ca. 80 dB(A)).…”
Section: Factory Workers Exhibited Small Changes In Pure-tone Threshocontrasting
confidence: 64%
“…Attenuation of fine structure following overexposure to noise (Engdahl and Kemp, 1996) as well as aspirin consumption (Brown et al, 1993;Rao and Long, 2011) or cisplatin exposure (McMillan et al, 2012) provides further support for this notion of sensitivity of fine structure to minor insults to the cochlea. Despite these findings, the sensitivity of fine structure to cochlear insult remains unclear as additional attempts to establish the relationship between fine structure and noise-induced changes in the cochlea have failed to yield clear results (e.g., Reuter and Hammershøi, 2007).…”
Section: Introductionmentioning
confidence: 95%
“…This result may reflect the fact that OAE are a measurement of cochlear motor activity due to outer hair cell action. Because hearing loss caused by high sound pressure levels starts with outer hair cell damage, [27][28][29][30][31] OAE may be more sensitive than pure tone audiometry to detect early changes due to exposure to amplified music. 4,7,16,25,26,31 Responses in the questionnaire on satisfaction with the HiFi ER 20 hearing protector were concentrated in the "agree" and "fully agree" groups, indicating a positive attitude towards using hearing protectors.…”
Section: Discussionmentioning
confidence: 99%